Konflik romantis dan komunikasi tidak efektif di era pesan singkat: Dampaknya terhadap kesehatan mental remaja dengan Tsrait Neurotisisme - Nurhalizah, Siti (Maliki Interdisciplinary Journal, 2025)
The rise of digital communication technologies has transformed the dynamics of adolescent romantic relationships. Instant messaging, while providing convenience and accessibility, often removes nonverbal cues that are vital for emotional understanding, thereby increasing the potential for miscommunication and conflict. This study aims to review the literature on how the personality trait of neuroticism moderates the effects of digital romantic conflict on adolescents’ mental health. Using a literature review combined with personal reflection, the findings reveal that text-based conflicts tend to trigger negative interpretation, rumination, and emotional dysregulation, leading to heightened anxiety, sleep disturbances, and decreased psychological well-being. Adolescents with high neuroticism levels exhibit stronger emotional reactivity to ambiguous digital messages, whereas emotionally healthy communication serves as a protective factor. The study highlights the need for digital communication literacy in schools, personality-informed counseling interventions, and technology design that promotes emotionally aware interactions.